Cotidiano escolar: a Escola Profissional de Franca (1924-1942) - Caraponale, Priscila Ferrer (2009)
Created by the state of Sao Paulo government in 1924, the Franca Professional School was part of a govern project that aimed at the enlargement of the professional institut ions throughout the state. In this research, dec i s i ve moments of the institution were elected and topics such as events tha t d e t ermined the city of Franca to get the institution, how its implantation occurred, how the activities elapsed during its first years, and the way the scholar quotidian went by were investigated. Through legal documents from the State Government and from the school, we intended to understand how the school absorbed the successive regulations and the impacts they had on the practice of the institution , as well as how the school served the local demands, therefore, it assumed a t four moments selected by this research, speci fic signs , relatively to its similar ones at the state. This research is linked to the Project History of School Subjects and Didactic Book, to the subproject Disciplinarization of Professional Knowledge that aims to investigate the histori c processes by which the professional knowledge was incorporated to school education, acquiring singular aspects in it